Synergistic effect of lean practices on lead time reduction: Mediating role of manufacturing flexibility - Nawanir, Gusman; Lim, Kong Teong; Thurasamy, Ramayah; Fatimah, Mahmud; Lee, Khai Loon; Mohd Ghazali, Maarof (Emerald, 2020)
Purpose: This study scrutinized the synergistic effects of lean manufacturing (LM) on lead time reduction (LR) while investigating the mediating role of manufacturing flexibility (MF) in that relationship within the context of batch and mass customization manufacturers.